Perovskite/perovskite planar tandem solar cells: A comprehensive guideline for reaching energy conversion efficiency beyond 30%. (January 2021) - Hossain, Mohammad Ismail; Saleque, Ahmed M.; Ahmed, Safayet; Saidjafarzoda, Ilhom; Shahiduzzaman, Md.; Qarony, Wayesh; Knipp, Dietmar; Biyikli, Necmi; Tsang, Yuen Hong
Abstract: Perovskite/perovskite tandem solar cells (Pk/Pk TSCs) have a substantial potential to outperform the Shockley-Queisser limit of single-junction solar cells. However, optimum material bandgap selection and device processability impede the progress in acquiring efficient Pk/Pk TSCs. The choice of charge transport/contact materials additionally has a significant influence on the photovoltaic performance of Pk/Pk TSCs. Hence, the actual fabrication of a two-terminal Pk/Pk TSC becomes tricky, which requires a detailed understanding of the underlying optical and electrical properties of the device. In this study, a wide bandgap (~1.72 eV) lead iodine-bromide (Pb–I–Br) and a narrow bandgap (~1.16 eV) tin lead-iodide (Sn–Pb–I) perovskite absorbers are considered as potential sub-cells for realizing highly efficient planar Pk/Pk TSCs. Furthermore, energetically associated hole and electron selective contacts are prepared by atomic layer deposition (ALD) of metal oxides. The optics of solar cells is investigated by three-dimensional finite-difference time-domain (FDTD) optical simulations, and finite element method (FEM) electrical simulations are exploited to determine realistic photovoltaic performance parameters. A comprehensive study is carried out to provide a complete guideline for the realization of energy conversion efficiency exceeding 30% in Pk/Pk TSCs. Graphical abstract: Image 1 Highlights: A detailed guideline to reach energy conversion efficiency beyond 30% is provided. An advanced coupled electromagnetic approach is adapted to investigate optoelectric effects of solar cells. An excellent agreement is found between the experimentally fabricated and numerical approach in single-junction solar cell. The optimized tandem solar cell estimates an energy conversion efficiency of ~31% under matching condition. Investigated results are further compared with the calculated theoretical upper limit (Shockley-Queisser limit).